Grassroots innovations in community-led housing in England: the role and evolution of intermediaries. Issue 1 (2nd January 2020) - Lang, Richard; Chatterton, Paul; Mullins, David
ABSTRACT: The paper aims to take forward recent research concerning the development of grassroots innovations and sustainability transitions in housing. We introduce and empirically assess a multi-level, process-oriented framework informed by strategic niche management (SNM) and social capital theory. Drawing on qualitative data, the empirical part explores the emergence of community-led housing (CLH) in England as a grassroots-based housing niche which operates in a context of market dysfunction. The paper offers further conceptual development of the role of intermediaries in grassroots niche building. Our findings suggest an evolution from independent sub-niche umbrellas to broader-based intermediaries to leverage and consolidate different sustainability practices in the niche. The results question an unadapted application of the simplistic growth-oriented SNM approach advocating for strategic coherence. In particular, our analysis shows that the development of broader-based intermediary organisations is driven by short-term government funding and carefully preserves the diversity of approaches and identities within the niche.